1991
DOI: 10.1002/chp.4750110304
|View full text |Cite
|
Sign up to set email alerts
|

Varying the format of CDE: Practitioners' perceptions of need and usefulness

Abstract: Continuing dental education (CDE) is the primary learning mechanism for practicing dentists. Consequently, practitioners' perceived need for CDE and their assessment of its usefulness should be continually evaluated. These issues were addressed during a continuing education initiative on fissure sealants. Of 677 dentists who were oflered CDE and responded to pre-and postintervention surveys, 78% selected one of three formats offered: a formal continuing education course, mailed written materials and a videotap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, when Woolfolk et al. (64) presented participants with a choice of CPD formats, 42% selected distance learning methods whilst only 17% chose traditional formal lecture courses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when Woolfolk et al. (64) presented participants with a choice of CPD formats, 42% selected distance learning methods whilst only 17% chose traditional formal lecture courses.…”
Section: Resultsmentioning
confidence: 99%
“…Abbott et al (56) found that half of the courses taken by their Australian participants were lecture courses or seminars with the remainder incorporating practical and clinical components. However, when Woolfolk et al (64) presented participants with a choice of CPD formats, 42% selected distance learning methods whilst only 17% chose traditional formal lecture courses.…”
Section: Continuing Professional Development Modes Of Deliverymentioning
confidence: 99%
“…The parenting style is influential because with a very tolerant parent the child is likely to be polite but on the other hand, in a family where the child is being bullied, he or she is more likely to behave inappropriately by following the family model. (Woolfolk, 2011) Bandura emphasizes the same with his theory, highlighting the fact that children tend to model their behavior by observing the social environment where they grow up. (Dragoti, 2012) Another factor is the individual and personal component which can be learned but there are also studies that claim that it may be innate, i.e.…”
Section: Introductionmentioning
confidence: 87%